Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijerph16183440
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of Nutrients Intake among Jordanian Pregnant Women in Comparison to Dietary Reference Intakes

Abstract: Objective: Maternal nutrition is considered an important pillar in the pregnancy outcomes for both mother and infant. A mother’s malnutrition and inadequate nutrient intake is associated with many undesirable pregnancy outcomes. Hence, assessing the nutritional status of the mother in the early stages of the pregnancy and preventing any inadequacy can preclude many health problems for both mother and infant. Therefore, this study aimed to assess the adequacy of nutrient intakes among Jordanian pregnant women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…Only 48.7% of the subjects met the RNI requirements for energy intake. This is similar to a study conducted among Jordanian mothers [26]. However, it is higher as compared to results reported by Manaf et al where only 21.9% of the respondents achieved the RNI requirement for energy [27].…”
Section: Resultssupporting
confidence: 88%
“…Only 48.7% of the subjects met the RNI requirements for energy intake. This is similar to a study conducted among Jordanian mothers [26]. However, it is higher as compared to results reported by Manaf et al where only 21.9% of the respondents achieved the RNI requirement for energy [27].…”
Section: Resultssupporting
confidence: 88%
“…Our results showed that while the intake of fruit, vegetables, and dairy products were comparable between the three trimesters, there was a significant increase in consumption of grains during the third trimester compared with the first and second trimesters. This could be attributed to the higher energy and total carbohydrate intake of our study participants in the third trimester compared with the first and second trimesters, as previously reported by Tayyem et al (2019) . Our results are in agreement with Huybregts et al (2009) who reported that the mean intake of cereals is higher in the third trimester [+45.2 g; 95% CI: −0.5; 90.9] compared with the first and second trimesters.…”
Section: Discussionsupporting
confidence: 74%
“…A large proportion of the participants in the first (68.0%), second (72.9%), and third (63.6%) trimesters of pregnancy had a college degree or above. Furthermore, 50.0%, 61.5%, and 58.1% of participants, respectively, had normal BMIs; 6.3%, 5.2%, and 2.9%, respectively, were underweight; 33.3%, 28.1%, and 26.5%, respectively, were overweight; and 10.4%, 5.2%, and 12.5 %, respectively, were obese ( Tayyem et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies determine dietary knowledge and beliefs during pregnancy using food consumption surveys [65][66][67]. In the case of the present study, the aim is to validate a questionnaire based on nutritional knowledge and beliefs and not just based on food consumption with a quantitative approach.…”
Section: Discussionmentioning
confidence: 99%